Pengaruh Model Project Based Learning Berbantuan Media Aplikasi Ipusnas terhadap Keterampilan Menulis Teks Ulasan Siswa Kelas VIII SMP Swasta Al-Washliyah 30 Medan T.A 2024/2025 - Siti Fatimah Handayani Hsb; Salmah Naelofaria (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to determine the project based learning model assisted by the iPusnas application media on the writing skills of review texts of class VIII students of Al-Washliyah 30 Medan private junior high school. The method used is a quantitative research method. The type of research used is experimental research using a two-group post-test design. The data analysis technique for this study uses normality tests, homogeneity tests, and hypothesis tests using SPSS ver 26. Through hypothesis testing, it is accepted with a significant value of 0.000 <0.05. It can be concluded that there is an influence of the project based learning model assisted by the iPusnas application media on the writing skills of review texts of class VIII students of Al-Washliyah 30 Medan private junior high school in the 2024/2025 academic year.